Seller opportunism in credence good markets: The role of market conditions - Katharina Momsen; Markus Ohndorf (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2022)
We report the results of an experiment to systematically investigate the influence of different settings in credence good markets on opportunism in the sellers' decisions. We find that, as predicted by a cognitive dissonance model, the specific choice of the design features might be less innocuous than generally presumed: sellers' decisions made under a direct sales regime are significantly more opportunistic than purchase recommendations. Furthermore, average choices are more opportunistic when a costless diagnosis is required to assess the buyer's needs - sellers exploit moral wiggle room by avoiding information. Yet, this effect is only present for purchase recommendations, not direct sales. Both of these effects significantly affect market efficiency. Generally, the parametrization of the decision problem has a strong influence on opportunism, as predicted. Here, we find that sellers tend to overtreat and buyers self-select into overtreatment.
Keywords: C90; D47; D82; D91; L15; 330; information avoidance; credence goods; moral wiggle room; norm activation model; online experiment